2017
DOI: 10.18520/cs/v112/i07/1421-1429
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Magnetic Ion-Doped Semiconductor Quantum Dots

Abstract: Dilute magnetic semiconductor (DMS) quantum dots (QDs) have potential to be used as basic working components of spin-based electronic devices. Therefore it is important to study these materials from fundamental and technological viewpoints. Quantum confinement effects are known to enhance exchange interactions and induce properties that were previously not observed in bulk materials. In fact, properties are known to alter dramatically when dimensions are reduced to nanometre size regime. In this review we brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
11
0
1
Order By: Relevance
“…It has been observed that the effectiveness of interaction of sp-d for the exchange of carrier and magnetic ions in terms of hole energy depends on the high and low magnetic field induces from outside. Hence, it is expected that due to the small size of a quantum dot, the exchange and interaction of d electrons with sp shelled electrons will be extensive in DMSQDs [56]. Therefore, the spintronics devices developed from DMSQDs are expected to be efficient as well as miniaturized one, probably due to the quantum confinement effect of DMS and therefore better than the single DMS materials.…”
Section: Dilute Magnetic Semiconductor Quantum Dots (Dmsqds)mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that the effectiveness of interaction of sp-d for the exchange of carrier and magnetic ions in terms of hole energy depends on the high and low magnetic field induces from outside. Hence, it is expected that due to the small size of a quantum dot, the exchange and interaction of d electrons with sp shelled electrons will be extensive in DMSQDs [56]. Therefore, the spintronics devices developed from DMSQDs are expected to be efficient as well as miniaturized one, probably due to the quantum confinement effect of DMS and therefore better than the single DMS materials.…”
Section: Dilute Magnetic Semiconductor Quantum Dots (Dmsqds)mentioning
confidence: 99%
“…Unwanted oxidation can also be prevented during the adopted during the synthesis process. Fe, Co, Ni and Mn are the main doping elements used for the preparation of DMSQDs of semiconductors of Group II-VI [56].…”
Section: Synthesis Of Dmsqdsmentioning
confidence: 99%
See 1 more Smart Citation
“…excitonic excited states introduced by strong dopant-carrier exchange coupling, red-shied PL emission bands arising from either the dopant d-d levels or the interaction of the dopant d level with the host, and several other applications. [20][21][22][23][24] The unpaired spins of these open shell transition metal dopants are magnetically or optically coupled to the free and photogenerated charge carriers, wherein the dopant-carrier spatial overlap determines the coupling strength. These sp-d exchange interactions are characteristic features resulting in magnetooptical and/or magneto-transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…The application of QDs for combined targeting and delivery of diagnostic and therapeutic agents can be further developed by a combination with magnetic separation techniques via the recent evolution of MQDs. In this chapter, among many benefits of MQDsbased separation to current procedures, one should also mention the small dimension of MQDs, which are small enough to possibly interact with single-cell biomarkers/cell surface receptors which results in corresponding quantification of the results [22,25]. These multifunctional fluorescent and magnetic nanoparticles of small dimension, which are MQDs, can target any biomolecule and can be separately controlled by engineering magnetic fields.…”
Section: Introductionmentioning
confidence: 99%